The Travel Diary of a Lithuanian Jesuit: Peregrination to Rome and Back in 1723–1724 - Kvizikevičiūtė, Milda (Senoji Lietuvos literatūra, 2017)
The manuscript of a travel diary (1723–1724) which was written by a Lithuanian Jesuit and is currently kept at the Lithuanian State Historical Archives, is a perfect example of an eighteenth-century peregrination to Rome. It reflects various aspects of travelling: technicalities of the travelling, visiting towns and cities, and phenomena interesting and unusual to the eye of the traveller from the Grand Duchy of Lithuania. This is an analysis of a travel diary written in Latin, which examines several different aspects of this particular peregrination and its diary: the itinerary and supposed reasons for choosing it, problems and inconveniences during the trip. There is also an analysis of the model of the description of towns and cities, by making distinction between longer and shorter visits (the latter are described in a more standard way). The main destination of the peregrination was the city of Rome, as the traveller went to the congregation of procurators in Rome, therefore, special attention is paid to this city and its description in the article: it follows the manner of the author of the diary, that is, by drawing a distinction between sacred and profane as well as ancient monuments in the city
Keywords: travel diary; travel literature; Italy; Rome; Jesuits